Assessment of the monumental trees health condition from Brasov area using Arbotom Sonic Tomograph - Diana VASILE; Constantin DUMITRU-DOBRE; Simona COMAN; Virgil SCĂRLĂTESCU; Iuliana-Gabriela BREABĂN; Raluca ENESCU (Present Environment and Sustainable Development, 2023)
The monumental trees growing in the cities, especially those from the parks, green spaces and alignments, which potentially cause a great risk to people, are required from time to time to be checked about their health conditions. The aim of this article was to assess the health state of the seven monumental trees from Brasov using ultrasonic tomography with an ARBOTOM 2D software (Rinn Tech, Germany). The material under research was the seven monumental trees that grows in Brasov area, respectively: silver fir tree, sweet chestnut tree, beech tree, ginkgo, horsechestnut tree, sycamore tree and plane tree, whose health status was checked using a sound tomograph which allows to assess the inside of the trunk in a non-invasive way. It could be observed that of the seven monumental trees investigated, two of them are in good status of health (Ginkgo tree and sycamore tree), three specimens show visible effect of decay processes of wood (65% horsechestnut tree, 75% sweet chestnut tree and 31% plane tree) and two specimens respectively silver fir tree and beech tree have the cross-section of their trunks with a beginning of rot in a percentage of 65%.